In Situ Modification of the Tumor Cell Surface with Immunomodulating Nanoparticles for Effective Suppression of Tumor Growth in Mice - Zheng, Chunxiong (Advanced materials (Deerfield Beach, Fla.), 2019)
© 2019 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.